Cerebellum regulating cerebral functional cortex through multiple pathways in complete thoracolumbar spinal cord injury - Zheng, Weimin; Wang, Ling; Yang, Beining; Chen, Qian; Hu, Yongsheng; Du, Jubao; Li, Xuejing; Chen, Xin; Qin, Wen; Li, Kuncheng; Lu, Jie; Chen, Nan (Frontiers in Neuroscience, 2022)
The previous studies have found significant brain structural and functional changes in cerebral regions after spinal cord injury (SCI), but few studies have explored the cerebellar–cerebral circuit changes in SCI. This study aims to study the brain structural changes of cerebellar subregions and its functional connectivity (FC) changes with cerebrum in complete thoracolumbar SCI (CTSCI), and screen out the regions that play relatively important roles in affecting sensorimotor function. Eighteen CTSCI patients and 18 age- and gender-matched healthy controls (HCs) were recruited. Voxel-based morphometry (VBM) was used to characterize the brain structural changes of cerebellar subregions [from the Anatomical Automatic Labeling (AAL116)], seed-based FC was used to evaluate the cerebellar–cerebral FC changes and support vector machine (SVM) analysis was used to search for sensitive imaging indicators. CTSCI patients showed slightly structural atrophy in vermis_3 (p = 0.046) and significantly decreased FC between cerebellum and cerebral sensorimotor-, visual-, cognitive-, and auditory-related regions (cluster-level FWE correction with p < 0.05). Additionally, SVM weight analysis showed that FC values between vermis_10 and right fusiform gyrus had the greatest weight in functional changes of CTSCI. In conclusion, different degrees of structural and functional changes occurred in each subregion of cerebellum following CTSCI, and FC change between vermis_10 and right fusiform gyrus plays the most important role in dysfunction and may become an important neural network index of rehabilitation therapy.